The role of platelets in antiphospholipid syndrome. (17th November 2017) - Baroni, G.; Banzato, A.; Bison, E.; Denas, G.; Zoppellaro, G.; Pengo, V.
Abstract: Despite extensive research, the pathogenesis of antiphospholipid syndrome (APS) remains obscure in many aspects. However, it is widely accepted that thrombosis is the result of a hypercoagulable state caused by antibodies directed against β2-glycoprotein I (β2-GPI), a protein whose physiological role is unknown. Although underestimated, platelets may be involved in APS and its thrombotic manifestations, especially arterial, in several ways. Thrombocytopenia is the most relevant non-criteria manifestation of APS, possibly caused by direct binding of anti-β2-GPI antibodies or anti-β2-GPI–β2-GPI complexes. On the other hand, platelets may have a key role in APS-related thrombosis due to the presence of multiple receptors that can interact with anti-β2-GPI antibodies (especially apolipoprotein E receptor 2' (apoER2') and glycoprotein Ibα (GPIbα)) with consequent release of different procoagulant mediators such as thromboxane B2, platelet factor 4 (PF4), and platelet factor 4 variant (CXCL4L1). The aim of this review is to put together evidence on the possible role of platelets in APS and to stimulate further research on the issue.